2018
DOI: 10.1371/journal.pone.0206758
|View full text |Cite
|
Sign up to set email alerts
|

Towards non-invasive characterisation of coronary stent re-endothelialisation – An in-vitro, electrical impedance study

Abstract: The permanent implantation of a stent has become the most common method for ameliorating coronary artery narrowing arising from atherosclerosis. Following the procedure, optimal arterial wall healing is characterised by the complete regrowth of an Endothelial Cell monolayer over the exposed stent surface and surrounding tissue, thereby reducing the risk of thrombosis. However, excessive proliferation of Smooth Muscle Cells, within the artery wall can lead to unwanted renarrowing of the vessel lumen. Current im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
(89 reference statements)
3
6
1
Order By: Relevance
“…Previous work reported in the literature with other cell types (e.g. smooth muscle cells) has shown similar changes in impedance which can be monitored to infer cell behaviour under culture conditions [17] and supports our findings. Table 1 shows the p values from a 2-sample t test performed on the normalized impedance magnitude data taken after 36 h. As expected from observation of the graphs, the p value at high frequencies is high.…”
Section: Normalized Impedancesupporting
confidence: 92%
“…Previous work reported in the literature with other cell types (e.g. smooth muscle cells) has shown similar changes in impedance which can be monitored to infer cell behaviour under culture conditions [17] and supports our findings. Table 1 shows the p values from a 2-sample t test performed on the normalized impedance magnitude data taken after 36 h. As expected from observation of the graphs, the p value at high frequencies is high.…”
Section: Normalized Impedancesupporting
confidence: 92%
“…Holland et al also investigated EIS for ISR, they used large working electrodes with an oversized counter electrode to evaluate SMCs and ECs in vitro that however these were not suitable for in vivo applications nor had an implant or data telemetry device been developed. [31] Like our work they identified that the impedance of the two cell types differed, hypothesizing that like other researchers the formation of cells tight junctions, cells morphology, and strength of adhesion played key roles in the detection. [21,32] In our work the changes in impedance are hypothesized to be due to the morphological changes of the cells and how those cells spread across the sensor surface.…”
Section: Appropriateness Of Eis For Cell Discernmentsupporting
confidence: 76%
“…There exist methods to monitor cell cultures in vivo based on their BI [17][18][19][20]. In [17], a cell-culture was transformed into a "biological oscillator" whose characteristic parameters (i.e., frequency, amplitude, phase, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Relevant parameters are extracted from the frequency and amplitude of the oscillations. In [20], primary cells were also cultured and characterized while conforming to the endothelium tissue.…”
Section: Introductionmentioning
confidence: 99%